Salivary profile and its relationship to the degree of immunosuppression in patients with hiv infection with and without highly active antiretroviral treatment - Vera Cruz, Moisés (2009)
The aim of this study was to evaluate the salivary profile of HIV-infected patients with and without Highly Active Antiretroviral Treatment (HAART), evaluating the Symptoms of salivary hypofunction (Xerostomia, Dysgeusia, Dysphagia, and Susceptibility to develop ulcers oral), the Unstimulated Salivary Flow Rate, Salivary pH and Salivary Viscosity, establishing their relationship with the degree of immunosuppression as assessed by the Counting of lymphocyte CD4/μl. We evaluated 126 patients with HIV infection with HAART and without HAART who were attended at the Health Strategy for Prevention and Control of STI, HIV and AIDS at the Hospital Nacional Dos de Mayo, Lima- Peru. Patients without HAART had significantly higher rates of some salivary hypofunction Symptoms: Xerostomia , Dysgeusia Dysphagia) and Susceptibility to develop oral ulcers and significantly higher values of Salivary viscosity but values were also significantly lower of Unstimulated Salivary Flow Rate and Salivary pH compared to patients with HAART. Furthermore, patients with a greater degree of immunosuppression had significantly higher rates of Symptoms of salivary hypofunction and Salivary Viscosit and significantly lower values of Unstimulated Salivary Flow Rate and Salivary pH ,compared to patients with a lower degree of immunosuppression. It was concluded that there was an alteration of the salivary profile of patients with HIV infection, which is significantly higher in patients without HAART and those with a greater degree of immunosuppression.